Invasion of alien plant species and their impact on different ecosystems of Panchase Area, Nepal - Baral, S.; Adhikari, A; Khanal, R.; Malla, Y.; Kunwar, R.; Basnyat, B.; Gauli, K.; Acharya, R. P. (Banko Janakari, 2017)
The aggressiveness of invasive alien plant species has been amidst the changing climate, which has necessitated further research in this area. The impact of invasive alien plant species in the Panchase area of Nepal was assessed through the forest resource assessment and other methodologies such as, household survey, group discussion, direct field observation, participatory cluster mapping, quadrat sampling, laboratory analysis, and GIS mapping. A total of nine major invasive species, in which Ageratum houstonianum and Ageratina adenophora were found spread throughout the ecosystem. The invasion was fueled by anthropogenic disturbances such as leaving the agricultural lands, fallow and degradation of habitat. As a consequence, native species such as Artemisia indica and Urtica dioica were outcompeted mostly in the fringes of fallow lands, agricultural lands and in the disturbed sites. The intrusion was, however, less in the forest area, implying that community-managed dense canopy forests are less susceptible to invasion and routine management can offset the negative effects of invasion. Even though many negative consequences of the invasion were observed in the study sites, the possibility of the economically exploiting the biomass of invasive alien plant species for generating income locally was noticed. Banko Janakari, Vol. 27, No. 1, page: 31-42